Hybrid Learning-based Instruction in Teaching Aviation English for Cadets – A Case Study at Vocational Higher Education Indonesia - Ahmad Rossydi; Haryanto Atmowardoyo; Sukardi Weda; Muliati Muliati (Yayasan Keluarga Guru Mandiri, 2023)
The project aims to develop a hybrid learning-based instructional paradigm that integrates both traditional face-to-face training and online learning methods. The study employed a qualitative research approach, utilizing case study approaches. The researchers carefully chose and ascertained the research participants to acquire a comprehensive understanding and insights into implementing hybrid learning at the Makassar Aviation Polytechnic. The study investigated one English lecturer and a class of 24 second-semester cadets enrolled in the Air Traffic Controller (ATC) study program. The researchers employed many tools to gather data and adhere to the Creswell theory of qualitative research methodologies in this study. The instruments utilized in this study encompassed observation instructions, interview guidelines, field notes, and documentation. The results indicate that the lecturer at Makassar Aviation Polytechnic can fully implement Hybrid Learning-based Instruction in the Aviation English class. Aviation English Learning encompasses three stages: planning, implementation through face-to-face meetings, and virtual learning cooperation involving synchronous and asynchronous modes. Additionally, self-paced asynchronous learning and evaluation are integral components of this process. The research has the potential to make significant contributions to the fields of science and education: 1) Enhanced Aviation Safety; 2) Innovative Pedagogy; 3) Data-driven Insights; 4) Application in Practice; 5) Contribution to the Literature; 6) Optimization of Learning Efficiency; 7) Adaptability in Learning; 8) Evaluation and Assessment; 9) Synchronous and Asynchronous Learning Modes; 10) Integration of Technology; 11) Cost-efficiency.